Reflections on the OECD guidelines for in vitro skin absorption studies - Hopf, N.B.; Champmartin, C.; Schenk, L.; Berthet, A.; Chedik, L.; Du Plessis, J.L.; Franken, A.; Frasch, F.; Gaskin, S.; Johanson, G.; Julander, A.; Kasting, G.; et al. (Regulatory toxicology and pharmacology, 2020)
At the 8th conference of Occupational and Environmental Exposure of the Skin to Chemicals (OEESC) (16–18 September 2019) in Dublin, Ireland, several researchers performing skin permeation assays convened to discuss in vitro skin permeability experiments. We, along with other colleagues, all of us hands-on skin permeation researchers, present here the results from our discussions on the available OECD guidelines. The discussions were especially focused on three OECD skin absorption documents, including a recent revision of one: i) OECD Guidance Document 28 (GD28) for the conduct of skin absorption studies (OECD, 2004), ii) Test Guideline 428 (TGD428) for measuring skin absorption of chemical in vitro (OECD, 2004), and iii) OECD Guidance Notes 156 (GN156) on dermal absorption issued in 2011 (OECD, 2011). GN156 (OECD, 2019) is currently under review but not finalized. A mutual concern was that these guidance documents do not comprehensively address methodological issues or the performance of the test, which might be partially due to the years needed to finalize and update OECD documents with new skin research evidence. Here, we summarize the numerous factors that can influence skin permeation and its measurement, and where guidance on several of these are omitted and often not discussed in published articles. We propose several improvements of these guidelines, which would contribute in harmonizing future in vitro skin permeation experiments. •OECD skin absorption guidelines should apply to all types of chemicals.•OECD Guidelines TGD428, GD28, and GN156 need to be harmonized.•Add detailed guidance on several sections (e.g., acceptable criteria, mass-balance).•Include theoretical basis of the skin permeation parameters.